Abdallah Bin Fodio's Technique for Translating the Quran Through Telling Prophetic Stories: An Analysis of West African Islamic Scholarship (British Journal of Multidisciplinary and Advanced Studies, 2024)
Abdallah bin Fodio, a prominent figure in West African Islamic scholarship during the 19th century, made significant contributions to Quranic translation by employing a unique technique that involved the integration of prohetic stories. This article explores the motivations, methodology, and impact of Abdallah bin Fodio's translation approach. By examining his translated texts and considering the historical and cultural context, this study sheds light on the distinctiveness and relevance of Abdallah bin Fodio's technique in the field of Quranic translation. The findings contribute to a deeper understanding of West African Islamic scholarship and its contributions to Quranic interpretation.